The Microfluidic Jukebox - Tan, Say Hwa (Nature Publishing Group, 2014)
Music is a form of art interweaving people of all walks of life. Through subtle changes in frequencies, a succession of musical notes forms a melody which is capable of mesmerizing the minds of people. With the advances in technology, we are now able to generate music electronically without relying solely on physical instruments. Here, we demonstrate a musical interpretation of droplet-based microfluidics as a form of novel electronic musical instruments. Using the interplay of electric field and hydrodynamics in microfluidic devices, well controlled frequency patterns corresponding to musical tracks are generated in real time. This high-speed modulation of droplet frequency (and therefore of droplet sizes) may also provide solutions that reconciles high-throughput droplet production and the control of individual droplet at production which is needed for many biochemical or material synthesis applications.